Review of an official opponent on the doctoral (Law) thesis by I. A. Efremova “Exemption institution in the criminal law theory and legislative and judicial practice”, majoring 12.00.08 - V. V. Sverchkov (Russian Journal of Economics and Law)
Objective: to assess the completeness and quality of the dissertation research carried out by I. A. Efremova on “Institute of exemption from punishment in the theory of criminal law, legislative and judicial practice”.Methods: dialectical approach to cognition of social phenomena, allowing to analyze them in their historical development and functioning, which contributed to applying the following research methods: logical, formal-legal, system, analytical, comparative-legal, sociological.Results: the theoretical model of convicts release from criminal punishment formed by the author is analyzed; the assessment is given of the regularities, tendencies and dependences established by the applicant, and of the new knowledge on the institute of release from criminal punishment and its norms.Scientific novelty: the advantages and disadvantages of the dissertation research are revealed; it is established that the dissertation research is an independent, complete scientific and qualification work, representing an advance in science and making a significant contribution to the development of the criminal policy of the state, including the doctrine of exemption from punishment.Practical significance: the main provisions and conclusions set out in the review can be used in scientific, pedagogical, law- making, and law-enforcement activities when considering the application and improvement of the institution of exemption of convicts from criminal punishment.